A simulation study of the effects of alcohol on driving performance in a Chinese population. (October 2016) - Li, Y.C.; Sze, N.N.; Wong, S.C.; Yan, Wei; Tsui, K.L.; So, F.L.
Abstract: Driving under the influence of alcohol (DUIA) is a significant factor contributing to road traffic crashes, injuries, and fatalities. Although the effects of alcohol on driving performance are widely acknowledged, studies of the effects of alcohol impairment on driving performance and particularly on the control system of Chinese adults are rare. This study attempts to evaluate the effects of alcohol on the driving performance of Chinese adults using a driving simulator. Method: A double-blind experimental study was conducted to evaluate the effects of alcohol impairment on the driving performance of 52 Chinese participants using a driving simulator. A series of simulated driving tests covering two driving modules, including emergency braking (EB) and following braking (FB), at 50 km/h and 80 km/h were performed. Linear mixed models were established to evaluate driving performance in terms of braking reaction time (BRT), the standard deviation of lateral position (SD-LANE), and the standard deviation of speed (SD-SPEED). Results: Driving performance in terms of BRT and SD-LANE was highly correlated with the level of alcohol consumption, with a one-unit increase in breath alcohol concentration (BrAC) degrading BRT and SD-LANE by 0.3% and 0.2%, respectively. Frequent drinkers generally reacted faster in their BRT than less-frequent drinkers and non-drinkers by 10.2% and 30.6%, respectively. Moreover, alcohol impairment had varying effects on certain aspects of the human control system, and automatic action was less likely to be affected than voluntary action from a psychological viewpoint. Conclusion: The findings should be useful for planning and developing effective measures to combat drink driving in Chinese communities.